TECHNIQUES OF TRANSLATING NOVEL I GOT YOUR NUMBER - Ariyantini, Diah (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
Some techniques are applied in translating positive politeness in order to get the equivalence of source language and target language. Those techniques are important to be applied in order to get a good translation. In translating positive politeness some problems often occurs such as: how the positive politeness will be translated and whether the translation of positive politeness in the source language equals with the target language. There are two kinds of research approaches used in this study: qualitative and quantitative approaches. This study used the document review in approaching the research problem rather than interview. In reviewing document this library research is performed in order to review some documents related to the main problems. Quantitative method deal with number and figure in analyzing the data. The finding shows that there are 11 types of positive politeness found in the novel such as : notice to hearer, exagerrate, address form, use in group dialect, contraction and ellipsis, seek agreement, avoid agreement, pressupose common ground, joke, offer and promise, include speaker and hearer in activity, ask for reason. Another result of the study is the type of technique used in tranlating the novel I Got Your Number as follows: adapation, amplification, literal, generalization, particularization, transposition, and calque.
Keywords: positive politeness, translation, and equivalence